RELATIONSHIP BETWEEN FOOD SKILLS AND HEALTHY FOOD PREFERENCE AMONG THE FEMALE ADOLESCENT IN ENUGU STATE, NIGERIA - Igwe , Amarachi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Previous studies have underscored the relevance of healthy food choices. However, the increasing dependence on convenient food among individuals at a younger age requires further inquiry on food choice. The present paper examined the relationship between food skills and healthy food preferences among adolescents. The participants comprised one hundred and ten (n=110) female students pooled from public and private tertiary institutions in the Enugu state of Nigeria. The respondents completed self-report measures. A correlational research design was employed for the study. The data collected from the respondents were analyzed using the statistical package for social sciences (SPSS version 23). A Pearson's product-moment correlation was performed to determine the correlation between food skills and healthy food preference. The analyses a statistically significant, moderate positive correlation between food skills and healthy food preference, r (108) = .41, p < .001. The result indicated that food skills explained about 21% of the variation in healthy food preferences.